First report of OXA-48-producing Klebsiella pneumoniae strains in Iran - Azimi, Leila; Nordmann, Patrice; Lari, Abdolaziz Rastegar; Bonnin, Rémy A. (German Medical Science GMS Publishing House, 2014)
[english] Carbapenem-resistant are increasingly reported worldwide and cause therapeutic problem in health care facilities. In this study 28 imipenem-resistant were examined for expression of carbapenemases by phenotypic and genotypic methods. Modified Hodge Test (MHT), CarbaNP test were used for phenotypic detection, and PCR using specific primers for the detection of and type carbapenemases with specific primers were performed. MHT and CarbaNP tests were positive for all of imipenem-resistant . The gene was detected in 27/28 isolates. One isolate was positive for the presence of the gene. According to our results NP test and MHT have high sensitivity and specificity for detection of those carbapenemases. This study reports the first cases of OXA-48-producing in Iran.